Multicomponent hexane isomers sorption on MOF ZIF-8 - Mendes, Patricia (2014)
The main goal of this research focuses on the development of an adsorptive process to separate hexane isomers (kinetic diameter very similar) in order to improve the quality of gasoline measured by the octane number (RON). In this investigation, studies of sorption equilibrium of hexane isomers: n-hexane (RON 25), 3-methylpentane (RON 75), 2,3-dimethylbutane (RON 103) and 2,2-dimethylbutane (RON 94) were performed on ZIF-8. The MOF ZIF-8 was synthesized and fully characterized by XRD, TGA, IR and surface area at the Institute Lavoisier Versailles.